2006
DOI: 10.1381/096089206775565177
|View full text |Cite
|
Sign up to set email alerts
|

Value of Preoperative Upper Endoscopy in Patients Undergoing Laparoscopic Gastric Bypass

Abstract: EGD is essential for diagnosis of GI diseases including tumors, ulcers, and hiatal hernias that alter the medical and surgical management of patients undergoing gastric bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 20 publications
6
58
0
3
Order By: Relevance
“…[51][52][53] The importance of preoperative endoscopy is supported by Sharaf et al 54 who found that 90% of their 195 patients had one or more lesions, with 60% that changed or delayed the clinical approach, including 3% Barrett's esophagus. Similarly, preoperative endoscopic findings reported by Zeni et al 55 from 169 patients, included in addition to two cases of Barrett's esophagus, one case of GIST and one case of gastric polyp that both necessitated a partial gastrectomy. The yield is higher if the endoscopy is symptom-oriented.…”
Section: Discussionmentioning
confidence: 70%
“…[51][52][53] The importance of preoperative endoscopy is supported by Sharaf et al 54 who found that 90% of their 195 patients had one or more lesions, with 60% that changed or delayed the clinical approach, including 3% Barrett's esophagus. Similarly, preoperative endoscopic findings reported by Zeni et al 55 from 169 patients, included in addition to two cases of Barrett's esophagus, one case of GIST and one case of gastric polyp that both necessitated a partial gastrectomy. The yield is higher if the endoscopy is symptom-oriented.…”
Section: Discussionmentioning
confidence: 70%
“…Other authors have reported the presence of gastric 15 and duodenal 16 NET in the preoperative setting. In fact, upper gastrointestinal endoscopy is recommended in the pre-bariatric surgery evaluation, 17 rendering possible the NET diagnosis before the surgical procedure. Al-Harbi et al 18 believe that gastric NETs are probably related to abnormal feeding behavior of the obese patients.…”
Section: Echocardiogrammentioning
confidence: 99%
“…En el contorno superior de ambos fragmentos, la flecha señala la unión gastro-esofágica. Palmer 8 en una revisión clásica, de 1.660 casos publicados, de tumores intramurales gástricos, los clasifica en: Leiomoma (37 a 56%), fibroma (17 a 30%), neurogénicos, (schwannomas o neurinemomas y neurofibromas) (5 a 16%), páncreas aberrante (5 a 13%), lipomas (2 a 6%), tumores de origen vascular (1 a 6%) y tumores quísticos (1 a 5%).…”
Section: Caso Clínicounclassified
“…La presencia de TIMG, son un hecho bien documentado 2,3,8,9 , si bien su incidencia global no supera el 1% de los pacientes sometidos a cirugía bariátrica y, siendo la mayoría de los casos hallazgos intraoperatorios, se recomienda efectuar una cuidadosa revisión gástrica durante la cirugía 3 , antes de confeccionar el reservorio gástrico. Zeni 2 , enfatiza el rol de la endoscopía de EED, como parte del estudio preoperatorio en estos pacientes.…”
Section: Caso Clínicounclassified
See 1 more Smart Citation